Air Oxidation of Carbon Spheres. II. Micropore Development - Michio Inagaki; Tetsuo Nishikawa; Kyoiti Oshida; Katsuya Fukuyama; Yoshikiyo Hatakeyama; Keiko Nishikawa (Adsorption Science & Technology)
The formation of micropores at the start of the oxidation of carbon spheres was studied by N 2 gas adsorption, small-angle X-ray scattering and transmission electron microscopy with the aid of image processing. On the basis of a detailed analysis of the measurement results, it was suggested that the principal process in the formation of micropores was the opening of closed pores initially present in the carbon matrix of the spheres. The fact that these closed pores were formed during carbonization as the nano-texture of glass-like carbons suggests that the carbonization process may govern the size of the micropores formed at the start of the oxidation process employed for activating such activated carbon precursors.